HUBUNGAN LAMA MENJALANI TERAPI HEMODIALISIS DENGAN KUALITAS HIDUP PASIEN PENYAKIT GINJAL KRONIK DI RUMAH SAKIT KHUSUS GINJAL RASYIDA - SARI DEVI; SHAHRUL RAHMAN (JURNAL ILMIAH KOHESI, 2022)
Chronic Kidney Disease (CKD) is a disorder of renal function that is progressive and irreversible where the body's abilitycannot maintain metabolism and electrolyte balance. Chronic Kidney Disease (CKD) is characterized by abnormalities inrenal structure or function with abnormal albumin excretion or decreased kidney function seen by examination of theGlomerular Filtration Rate (LFG) which lasts for more than 3 months. Patient with GFR less than 15ml/min/1,73m2 requiringRenal Replacement Therapy (RRT) such as hemodialysis. Hemodialysis is a theraphy that takes a long time, havecomplications, and require patient compliance. This condition will provide physiological and psychological stressors ofpatients wich can affects the quality of life of patients. This study aimed to determine relationship the long-time undergoinghemodialysis therapy with the quality of life of patients with chronic kidney disease on Rasyida Kidnet Special Hospital in2020 Descriptive-analytical with cross sectional approach onvolving 32 respondents of chronic kidney disease patientsundergoing hemodialysis. This study uses primary data using the Kidney Disease Quality Of Life Short-36 (KDQOL-36)questionnaire. There were 15 patients (46.9%) who underwent hemodialysis for more than 12 months and 9 of them had agood quality of life and 6 others had a poor quality of life. Statistical test results using the Chi Square Test obtained p value =0.036 (p <0.05). It can be concluded that there is a significant relationship between the length of undergoing hemodialysisand the quality of life of patients with chronic kidney disease.